Legal Protection for Third Parties Against Actio Pauliana Lawsuits in Bankruptcy Cases in Indonesia - Aimee Malca Luwinanda; Otih Handayani (Publication of the International Journal and Academic Research, 2024)
This research pertains to the legal protection of third parties against lawsuits of Actio Pauliana resulting from losses due to the annulment of legal acts regarding debt payment transfer transactions settled by PT. SINAR MAS MULTIFINANCE. However, it turned out that the assets already paid entered into the bankruptcy estate. The author of this research employs a normative juridical method utilizing the Civil Code and Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations connected with the case under examination, with the aim of understanding the legal protection of third parties as bona fide purchasers according to the legal sources used to analyze Case Number 02/Pdt.Sus/Actio Pauliana/2017/PN.Niaga.Jkt.Pst. The research findings indicate that the resolution has fulfilled the elements within the provisions to settle Actio Pauliana cases in bankruptcy scenarios; however, the execution of the bankruptcy estate cannot be carried out by the commercial court as it falls within the jurisdiction of the District Court. The third-party fulfills the element of being a bona fide purchaser by making payment according to market value, unaware that the purchased goods were assets of the bankruptcy estate. Therefore, legal remedies that can be pursued include filing for Cassation and Judicial Review (PK). Suppose the third party fails in these legal processes. In that case, compensation shall be awarded in accordance with Article 49 paragraph (4) of Law Number 37 of 2004 concerning bankruptcy and PKPU becoming part of the creditors of PT. SUMBER URIP SEJATI UTAMA as concurrent creditors.